Ukraine : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper analyses the impact that rising energy import prices might have on growth and inflation in Ukraine. The paper examines how rising gas prices might elevate macrofiscal risks in Ukraine's state enterprise sector. It assesses Ukraine's equilibrium exchange rate mainly based on the macroeconomic balance approach, and provides an account of the monetary framework debate. The paper also summarizes the current framework's achievements and shortcomings, and looks at traditional criteria for determining whether a peg or float fits Ukraine's economic characteristics.